Peran Preventif Dan Kuratif Notaris Dalam Sengketa Waris - M Adi Saputra; Firdaus Akbar; Dewi Mulyati (Marwah Hukum, 2026)
Inheritance disputes constitute one of the most prevalent family conflicts in Indonesia, primarily caused by unclear testamentary intentions, differing perceptions of fairness in inheritance distribution, and limited public understanding of the pluralistic inheritance law system. The coexistence of customary law, Islamic law, and civil law often leads to legal uncertainty and increases the potential for disputes among heirs. In this context, notaries play a strategic role as public officials authorized to draw up authentic deeds and provide legal certainty and protection. This study aims to analyze the preventive and curative roles of notaries in inheritance disputes, particularly through the drafting of wills, certificates of inheritance, and inheritance distribution deeds, as well as their involvement in non-litigation dispute resolution. This research employs a normative juridical method using statutory and conceptual approaches. The findings reveal that notaries perform a preventive role by preventing inheritance disputes through the preparation of authentic deeds and legal counseling, and a curative role at the pre-litigation stage by facilitating agreements and conducting non-litigation mediation. Nevertheless, the authority of notaries is strictly limited once inheritance disputes enter judicial proceedings.